Mulheres rurais na luta pela água: construções do desenvolvimento no Semiárido Paraibano - Pereira, Priscila Sousa (2021)
This dissertation discusses the incorporation of a gender perspective in the formulation and implementation of water policies and the social struggles of rural women for access to water, in the semiarid region of Paraíba. Authors such as: Scott (1995), Heleieth Saffioti, (1997), Durval Muniz de Albuquerque Júnior (1988), Ana Maria quiroga (1984), Maria Antônio de Alonso Quiroga (1985), Pierre Bourdieu (1999) and others were used. The general objective is to study public policies on access to water and the life experiences and social struggles of rural women in the semiarid region of Paraíba. The research had a qualitative approach and was developed in the Sitio Chapada community, municipality of Imaculada, state of Paraíba. For the production of research data, semi-structured interviews were carried out with eighth rural women, combined with a survey of documents related to public policies for access to water. The issue of water for rural populations in the semiarid region of Paraíba is part of a broader and more complex discussion, which articulates power and power relations; sexual division of labor; social organization, and development. The established emergency front public policy was one of the actions that most represented in the 80s and 90s to combat the adversities of droughts and access to water. But initially, women were excluded, which led to struggles to be included in the program. In the first decade of the 20th century, through the organization and implementation of the Brazilian Semiarid Articulation, the One Million Cisterns program was created, innovating with the construction of cisterns to capture rainwater, which brought more dignity to women. In the demand for the emergence of new families, the Coopered Project was created through the government of the state of Paraiba, with funding from the World Bank, for the construction of new cisterns in the state's poor and needy communities. Even though they are not, in general, family providers, women also play an extremely important role in providing financial assistance in their homes, although the man remains the head and has more political recognition. In the sertão, this reality persists and they are not always engaged in paid activities, built from a perspective centered on patriarchal power. However, it plays in the imagination of women how water was associated with religious festivities, erudite knowledge, sentimental sensations with luck and abundance, and sensuality around water as life. I conclude that the reflections of this study collaborate to update the vision that one should have of the role of women in different moments related to water, in different scenarios, and in social contexts.